2002
DOI: 10.1046/j.1464-2662.2001.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to HIV treatment: results from a 1‐year follow‐up study

Abstract: SummaryWe evaluated adherence to HIV treatments every 4 months during one year in 63 HIV-infected subjects using combination therapies including a protease inhibitor. A total of 18 subjects reported a high level of adherence, 14 in two evaluations, and eight a low level of adherence in all the three evaluations. The remaining 23 subjects (36.5%) reported different levels of adherence to treatment in the three evaluations. These ®ndings suggest that the level of adherence to treatment changes markedly for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…Martini et al (2002) found that patient satisfaction with the clinician-patient relationship was related to adherence (number of medication errors in 2 months) in outpatients with HIV in an Italian multicenter study. In a correlational study of 707 outpatients, Bakken et al (2000) found that patients who were more engaged with their providers evidenced better adherence to medications and appointments and better immune health than their less-engaged peers.…”
Section: Introduction the Patient-clinician Relationship Influences Gmentioning
confidence: 99%
“…Martini et al (2002) found that patient satisfaction with the clinician-patient relationship was related to adherence (number of medication errors in 2 months) in outpatients with HIV in an Italian multicenter study. In a correlational study of 707 outpatients, Bakken et al (2000) found that patients who were more engaged with their providers evidenced better adherence to medications and appointments and better immune health than their less-engaged peers.…”
Section: Introduction the Patient-clinician Relationship Influences Gmentioning
confidence: 99%
“…O auto-relato tem sido uma fonte de informação muito usada para identificação da conduta de adesão, pela acessibilidade e praticidade 21,22 . No entanto, o auto-relato tem aspectos limitadores como a memória, o nível sócio-cultural e o relacionamento com a equipe de saúde, que podem influenciar a veracidade dos relatos dos pacientes.…”
Section: Introductionunclassified
“…Medication type was not explicitly mentioned in four studies,37,38,45,59 but we assumed CPMM was used since CPMM is the standard medical treatment for the 20 selected diseases in this review. In most studies, patients were recruited from medical clinics or hospitals and the sample size ranged from 50–1,911.…”
Section: Resultsmentioning
confidence: 99%